The Role of PPATK in Proving Money Laundering Crimes - Adhar,; Amiruddin,; Sabardi, L. (International Journal of Scientific Research and Management (IJSRM), 2019)
The research aims to find out the PPATK’s Duties and Authorities in Law 8 of 2010 concerning Prevention and Eradication of Crime of Money Laundering and the Role of the PPATK in Proving Money Laundering Crimes.Duties and Authorities of PPATK in Law 8 of 2010 concerning Prevention and Eradication of Money Laundering Crimes. The aim of the PPATK is to Prevent and Eradicate Money Laundering Crimes, thus giving birth to an authority, namely 1). Collect, conclude, collect, analyze, evaluate information obtained from financial service providers, make guidelines on procedures for reporting suspicious financial transactions, 2). Provide advice and assistance to other authorized agencies regarding information obtained in accordance with the provisions of the Act on Money Laundering, 3). Provide recommendations to the government regarding the prevention and eradication of criminal acts of money laundering, 4). Report the results of analysis of financial transactions that indicate criminal acts of money laundering to the police for the purposes of investigation and prosecution for the purposes of prosecution and supervision, and 5). Make and submit reports on the analysis of financial transactions and other activities periodically to the President, Parliament, and institutions authorized to supervise Financial Service Providers (PJK). The role of PPATK in Proof of Money Laundering is PPATK in eradicating criminal acts of money laundering if it finds indications of suspicious transactions, cash transactions over five hundred million rupiahs, or transfers from and or abroad PPATK submits the results of investigations to investigators for investigation. In this case the PPATK only conducts the final assessment of the entire process of problem identification, analysis, evaluation of suspicious financial transactions conducted independently, objectively and professionally. However, the role of PPATK is very decisive in the process of identifying money from original crimes as evidence for investigators in proving the crime of money laundering.